Recirculated Process Water in the Flotation of Sulfides - Ngau, Michael (Department of Chemical Engineering, 2024)
Water scarcity has affected the availability, quality, and quantity of water available for use at water-intensive mineral processing concentrator plants. In response, more sustainable water reuse strategies have gained traction and proved beneficial by reducing used water effluents and freshwater withdrawals through the recycling of effluent water. The performance of concentrates using recycled water has been a headline topic of research. However, water recycling leads to a change in water quality in terms of species present in solution and physio-chemical properties, to the detriment of the flotation performance of sulfide ore. Froth stability is the ability of the foam to resist bubble coalescence and bubble bursting and is an integral property of the pulp with implications for flotation recovery and selectivity. This study investigates the impact of a change in water quality through the consecutive recycling of recovered tailings water, using a filter press to separate the tailings solids from batch flotation tests of a UG2 ore. The study investigated the impact of the addition of recycled water to the sequential milling and batch flotation tests of a UG2 ore on the froth stability of the tailings slurry and recovered water samples from the tailings and concentrate slurry. The experimental methodology developed in this paper was developed to: (1) monitor the accumulation of compounds and elements in the process water through the comminution and flotation facilities; (2). Investigates the impact of point of addition of recirculated water (i.e. to the mill or the float cell.). (3) Investigate the impact water recirculation on froth stability, pulp chemistry, mass and water recovery, coagulation and the grade and purity of sulphide concentrates. The techniques utilized in the project were as follows: (1) Pulp chemistry analysis using a multiprobe meter to analyse electrical conductivity (EC), pH, Dissolved Oxygen (DO%); Oxidative Redox Potential (mV) (2) Compound and elemental analysis and coagulation through UV/Vis and X-Ray fluorescence (3) Foam and Froth stability measurements of the tailings pulp and recovered water samples. The technique used to evaluate froth stability was a dynamic froth stability tests that observes the build-up of a set sample volume of slurry or recovered water sample in a non-overflowing froth column, agitated and aerated with a constant air feed of 7 L/min, measured and monitored for 20 minutes. The Bikkermans stability parameter and kinetic models of build-up were developed from experimental values to establish theoretical maximum froth height, bubble lifetime, and gas holdups of foams and froths was developed. Water recirculation leads to a change in the water quality and an increase in froth and foam stability due to the increase in the concentration of ions reducing the electrostatic stabilisation, leading to the formation of smaller bubbles with an improved resistance to coalescence and rupture, developing high froths visible from the different in maximum froth. The change in water quality also impacts the bubble lifetime, leading to longer bubble lifetimes, which slow down the froth development visible in the kinetic models developed. The point of addition of recirculated leads to a difference in the foam and froth stability, with recycling to the float cell achieving a higher froth stability due to higher ionic concentrations. Water recirculation lead to a increase in the solids and water recovery compared to baseline tests with float recirculation recovering 20 % more solids and 17 % more water as compared to mill recirculation at a higher recovery rate. Concurrently higher Cu recoveries when using recycled water, especially when recycled to the float cell, however reduced the grade of sulphides recovered due to an increase in gangue entrainment. This due to the higher ionic strength of the recycled water as observed in the higher concentrations of Ca2+, Mg2+, SO4 2- , Cl- , and higher EC, which are especially higher in float cell recirculated water. In addition, the residual reagent concentrations present in the tailings water samples were at ppm level due to high reagent mineral interaction. The significant decrease in DO% in mill recirculation's shows the impact of galvanic interactions on the pulp chemistry. In conclusion water recycling is a viable and efficient water reuse strategy that should be employed due to the improved recoveries, with keen monitoring of grades achieved.